Risky choice in the limelight - van den Assem, Martijn J.; Baltussen, Guido; van Dolder, Dennie (Massachusetts Institute of Technology Press, 2015)
This paper examines how risk behavior in the limelight differs from that in anonymity. In two separate experiments we find that subjects are more risk averse in the limelight. However, risky choices are similarly path dependent in the different treatments. Under both limelight and anonymous laboratory conditions, a simple prospect theory model with a path-dependent reference point provides a better explanation for subjects’ behavior than a flexible specification of expected utility theory. Additionally, our findings suggest that ambiguity aversion depends on being in the limelight, that passive experience has little effect on risk taking, and that reference points are determined by imperfectly updated expectations.